Beyond the strain recoverability of martensitic transformation in NiTi. (May 2019) - Heller, L.; Šittner, P.; Sedlák, P.; Seiner, H.; Tyc, O.; Kadeřávek, L.; Sedmák, P.; Vronka, M.
Abstract: Tensile deformation of a medical grade NiTi wire was investigated in a wide temperature range from −100 °C to 450 °C. Supplemental in-situ electrical resistance, synchrotron x-ray diffraction, digital image correlation and ex-situ TEM methods were employed to characterize deformation/transformation processes acting at high temperatures and stresses. Conventional superelastic deformation due to stress induced martensitic transformation taking place around room temperature becomes gradually accompanied by dislocation slip in the temperature range 30–80 °C. With further increasing temperature, stress induced martensitic transformation still proceeds in localized manner but the length of the forward stress plateau increases, volume fraction of the martensite phase at the end of forward stress plateau decreases, unrecovered strain increases and {114} austenite twins appeared in the microstructure of deformed wires. These observations were explained by the activity of a new deformation mechanism - stress induced B2=>B19´=>B2 T martensitic transformation into twinned austenite coupled with dislocation slip. Thermodynamic and crystallographic aspects of this B2=>B19´=>B2 T martensitic transformation breaking the strain recoverability limit of cubic to monoclinic martensitic transformation were outlined. To rationalize the observed thermomechanical responses of the wire at elevated temperatures, a TRIP like deformation mechanism based on this transformation was incorporated into an existing constitutive model of thermomechanical behaviors of NiTi. The model was numerically implemented into finite element code, simulations were performed and compared with the experimentally observed behaviors. It was found that the B2=>B19´=>B2 T martensitic transformation destroys the shape memory functionality of NiTi but renders it excellent ductility in thermomechanical loads, introduces nanoscale heterogeneity into its austenitic microstructure and allows for its low temperature processing and shape setting. Graphical abstract: Image 1 Highlights: TRIP like deformation of NiTi involving B2=>B19´=>B2 T martensitic transformation coupled with dislocation slip. Crystallographic and thermodynamics aspects of the two step B2=>B19´=>B2 T transformation. Constitutive model describing TRIP like deformation of NiTi including low temperature processing and shape setting. Strain localization and necking in tensile test Nanoscale heterogeneity introduced into the austenitic microstructure by the B2=>B19´=>B2 T transformation.